The Interaction between Explicit and Relational Incentives: An Experiment - Randolph Sloof; Joep Sonnemans (Tinbergen Institute, 2009)
We consider repeated trust game experiments to study the interplay between explicit and relational incentives. After having gained experience with two payoff variations of the trust game, subjects in the final part explicitly choose which of these two variants to play. Theory predicts that subjects will choose the payoff dominated game (representing a bad explicit contract), because this game better sustains (implicit) relational incentives backed by either reputational or reciprocity considerations. We also explicitly test how game choice is affected by the length of the repeated game.
Keywords: C91; M52; J41; 330; relational contracts; explicit incentives; crowding out; experiments; Wiederholte Spiele; Vertrauen; Arbeitsvertrag; Unvollständiger Vertrag; Implizite Kontrakte; Test